Comprehensive time-course gene expression evaluation of high-risk beef cattle to establish immunological characteristics associated with undifferentiated bovine respiratory disease - Scott, Matthew A.; Valeris-Chacin, Robert; Thompson, Alexis C.; Woolums, Amelia R.; Karisch, Brandi B. (Frontiers in Immunology, 2024)
Bovine respiratory disease (BRD) remains the leading infectious disease in beef cattle production systems. Host gene expression upon facility arrival may indicate risk of BRD development and severity, however a time-course approach would better define how BRD development influences immunological and inflammatory responses after disease occurrences. Here, we evaluated whole blood transcriptomes of high-risk beef cattle at three timepoints to elucidate BRD-associated host response. Sequenced jugular whole blood mRNA from 36 cattle (2015: n=9; 2017: n=27) across three timepoints (n=100 samples; days (D) 0, 28, 63) were processed through ARS-UCD1.2 reference-guided assembly (HISAT2/Stringtie2). Samples were categorized into BRD-severity cohorts (Healthy, n=14; Treated 1, n=11; Treated 2+, n=11) via frequency of antimicrobial clinical treatment. Assessment of gene expression patterns over time within each BRD cohort was modeled through an auto-regressive hidden Markov model (EBSeq-HMM; Posterior probability >0.5, FDR <0.01). Mixed-effects negative binomial models (glmmSeq; FDR <0.05) and edgeR (FDR <0.10) identified differentially expressed genes between and across cohorts overtime. A total of 2580, 2216, and 2381 genes were dynamically expressed across time in Healthy, Treated 1, and Treated 2+ cattle, respectively. Genes involved in the production of specialized resolving mediators (SPMs) decreased at D28, then increased by D63 across all three cohorts. Accordingly, SPM production and alternative complement were differentially expressed between Healthy and Treated 2+ at D0, but not statistically different between the three groups by D63. Magnitude, but not directionality, of gene expression related to SPM production, alternative complement, and innate immune response signified Healthy and Treated 2+ cattle. Differences in gene expression at D63 across the three groups were related to oxygen binding and carrier activity, natural killer cell-mediated cytotoxicity, cathelicidin production, and neutrophil degranulation, possibly indicating prolonged airway pathology and inflammation weeks after clinical treatment for BRD. These findings indicate genomic mechanisms indicative of BRD development and severity over time.